Assessment of the contemporaneous impacts of GDP and renewable energy consumption, applying the Dynamic Panel Data: Evidence from developed countries - Darvishi, Hadi; Varedi, Shayesteh (International Journal of Energy Economics and Policy, 2018)
The vast majority of the investigations analyze the effect of renewable energy utilization on GDP with single equation model and the others utilize dynamic panel data. The motivation behind this investigation is to build up a concurrent equations model to investigate the collaboration amongst GDP and sustainable power utilization in a dynamic panel data. This model uses GDP and renewable energy consumption as endogenous variables and seven factors as exogenous variables. By using a dynamic panel data of 30 developed countries from 1990 to 2015, with using the two-stage least-squares method. The results confirm the important influence of renewables and non-renewables as well as capital and labor force on GDP in developed countries. Also both GDP and real oil price play an important role in renewable energy consumption. Our findings suggest that energy planners and policy makers need to increase renewable energy investment to ensure sustainable economic development in future. Keywords: Simultaneous Equations, GDP, Renewable energy consumption. JEL Classifications: C30, F62, Q42